Reports of parents of children with autism on the formal supporting network: aspects of the parental diagnostic elaboration - Márcia Rejane Semensato; Cleonice Alves Bosa (Universidade Federal de Santa Maria (UFSM), 2013)
This article presents evidence about aspects that participate in the process of elaborating the diagnosis of autism by the parents, especially about the supporting network. This network tends to be one of the essential aspects considered by the parents in the restructuring the family and it is represented primarily by professionals and health services. It is presumed that these beliefs are important in the way that parents deal with the diagnosis and the choices they make for the child and the family, for example, schools and clinical services that are chosen. Therefore, a Content Analysis was performed on six interviews of parents of children who have had a diagnosis of autism. These interviews explored the family history of these couples and their experience since the diagnosis of the son. The results showed the parental beliefs related to the sense of support or helplessness in relationship with professionals and child care related services, since the diagnostic evaluation up to the communication of the diagnosis and interventions. These results presented evidence that the relationship with the professionals can be seen both as an alliance and as a source of stress.